2021
DOI: 10.1097/qco.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular phase of extracellular respiratory tract bacterial pathogens and its role on pathogen-host interactions during infection

Abstract: Purpose of review An initial intracellular phase of usually extracellular bacterial pathogens displays an important strategy to hide from the host's immune system and antibiotics therapy. It helps the bacteria, including bacterial pathogens of airway diseases, to persist and eventually switch to a typical extracellular infection. Several infectious diseases of the lung are life-threatening and their control is impeded by intracellular persistence of pathogens. Thus, molecular adaptations of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In addition to resistance, intracellular survival and biofilm formation also contribute to antibiotic treatment failure (11,12). Although considered essentially as extracellular pathogens, E. coli, K. pneumoniae and A. baumannii may also behave as opportunistic intracellular organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to resistance, intracellular survival and biofilm formation also contribute to antibiotic treatment failure (11,12). Although considered essentially as extracellular pathogens, E. coli, K. pneumoniae and A. baumannii may also behave as opportunistic intracellular organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little is known of how NTHi survives and traffics within this environment. Transcriptional factors, such as the ferric uptake regulator cassette which regulates the expression of multiple genes controlling the uptake and utilization of iron, and IgaB that cleaves lysosomal‐associated membrane protein‐1, appear to be important, and NTHi can survive for at least 72‐h inside AECs 90,91 …”
Section: How Nthi Establishes Lower Airway Infectionmentioning
confidence: 99%
“…Transcriptional factors, such as the ferric uptake regulator cassette which regulates the expression of multiple genes controlling the uptake and utilization of iron, and IgaB that cleaves lysosomal-associated membrane protein-1, appear to be important, and NTHi can survive for at least 72-h inside AECs. 90,91 Furthermore, lung explant cultures from COPD and CF patients undergoing transplantation for end-stage lung disease revealed that despite negative sputum and lung tissue cultures, NTHi was detected widely throughout the lung parenchyma and lower airway tissue sections by immunoperoxidase staining and polymerase chain reaction assays. 85 While most NTHi were detected in clusters in extracellular and paracellular locations, in CF patients they were found within macrophages too.…”
Section: Persistence and Survival Of Nthi In The Lungsmentioning
confidence: 99%
“…Pathogens responsible for lung diseases have been classified on how they replicate either inside or outside the host cell as extracellular, obligated intracellular, or facultative intracellular. Intracellular pathogens can hide or escape from the immune system and antibiotics by surviving the host's defense mechanism, cellular adhesion to invade the host, and adapting to the intracellular environment of the host (Lamberti & Surmann, 2021).…”
Section: The Lungsmentioning
confidence: 99%